A Numerical Study of Scalable Cardiac Electro-Mechanical Solvers on HPC Architectures - Colli Franzone, Piero; Pavarino, Luca F.; Scacchi, Simone (Frontiers in Physiology, 2018)
We introduce and study some scalable domain decomposition preconditioners for cardiac electro-mechanical 3D simulations. The electro-mechanical model of the cardiac tissue is composed of four coupled sub-models: 1) the static finite elasticity equations for the transversely isotropic deformation of the cardiac tissue; 2) the active tension model describing the dynamics of the intracellular calcium, cross-bridge binding and myofilament tension; 3) the anisotropic Bidomain model describing the evolution of the intra- and extra-cellular potentials in the deforming cardiac tissue; and 4) the ionic membrane model describing the dynamics of ionic currents, gating variables, ionic concentrations and stretch-activated channels. This strongly coupled electro-mechanical model is discretized in time with a splitting semi-implicit technique and in space with isoparametric finite elements. The resulting scalable parallel solver is based on Multilevel Additive Schwarz preconditioners for the solution of the Bidomain system and on BDDC preconditioned Newton-Krylov solvers for the non-linear finite elasticity system. The results of several 3D parallel simulations show the scalability of both linear and non-linear solvers and their application to the study of both physiological excitation-contraction cardiac dynamics and re-entrant waves in the presence of different mechano-electrical feedbacks.